2011
DOI: 10.1002/per.807
|View full text |Cite
|
Sign up to set email alerts
|

General Belief in A Just World and Resilience: Evidence from A Collectivistic Culture

Abstract: Previous research showed that in the individualistic culture, adults endorse the personal more than the general belief in a just world (PBJW vs. GBJW). Comparatively little is known about the prevalence character and adaptive functions of GBJW, especially in the collectivistic culture. We conducted three surveys among the Chinese adults and adolescents. We found that (1) Chinese adults and adolescents endorsed more GBJW than PBJW; (2) Adult survivors with high exposure to post‐earthquake trauma and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 88 publications
(125 reference statements)
7
77
1
6
Order By: Relevance
“…Nevertheless, we consider this study as an important step towards the reconceptualization of the functions of PBJW and GBJW, at least in Western societies (for a reconceptualization of BJW in China, see Wu et al, 2011, Wu et al, 2013. This study also highlights the importance of considering the victimization situations in the social context and the social groups in which they actually occur.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, we consider this study as an important step towards the reconceptualization of the functions of PBJW and GBJW, at least in Western societies (for a reconceptualization of BJW in China, see Wu et al, 2011, Wu et al, 2013. This study also highlights the importance of considering the victimization situations in the social context and the social groups in which they actually occur.…”
Section: Discussionmentioning
confidence: 89%
“…Consistent with that possibility, we found that acceptance of death prior to the loss was negatively associated with two symptoms at both 6 and 18 months post-loss: feeling disbelief or emotional numbness and a feeling that life is empty or meaningless. Similarly, beliefs in a just world, which may aid in the persistence of hope that the world retains meaning despite personal tragedies (Wu et al, 2011), were negatively associated with feelings that life is empty or meaningless at 6 months post-loss.…”
Section: Discussionmentioning
confidence: 99%
“…Future research will also be needed to consider the potential for additional nuance in linking justice to stress reactivity. For example, beliefs about justice for others might be associated with stress responses in other cultural contexts, or with cognitive and biological stress responses that were not presently considered (for related research, Wu et al, 2011). …”
Section: Discussionmentioning
confidence: 99%